Designing Air Intake System for Engine Performance and Efficiency Optimisation - Mohamed Faiz bin Mohamed Amin, Mohamed Faiz (2008)
This study is aimed to study the feasibility of using fish scale as the adsorbent to remove heavy metal from its aqueous solution. The adsorption nature of three types of metals namely Copper (Cu), Nickel (Ni) and Lead (Pb) on fish scale are studied independently, in a binary metal environment, where another competitive metal is also present during the adsorption process and finally in a continuous adsorption process.